2016
DOI: 10.15171/joddd.2016.017
|View full text |Cite
|
Sign up to set email alerts
|

The effect of ZnO nanoparticle coating on the frictionalresistance between orthodontic wires and ceramic brackets

Abstract: Background. Any decrease in friction between orthodontic wire and bracket can accelerate tooth movement in the sliding technique and result in better control of anchorage. This study was carried out to evaluate frictional forces by coating orthodontic wires and porcelain brackets with zinc oxide nanoparticles (ZnO).Methods. In this in vitro study, we evaluated a combination of 120 samples of 0.019×0.025 stainless steel (SS) orthodonticwires and 22 mil system edgewise porcelain brackets with and without spheric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(53 citation statements)
references
References 24 publications
(19 reference statements)
1
52
0
Order By: Relevance
“…These results agree with Kachoei et al 14 Scanning electron microscope images showed spherical ZnO nanoparticles with particle size ranging from 25 to 30 nm. Behroozian et al 19 used SEM technique to evaluate surface pattern of ZnO nanoparticles deposition and showed the presence of spherically shaped ZnO nanoparticles on the wire. Kachoei et al 20 confirmed a uniform coating of spherical shaped ZnO nanoparticles on stainless steel wires with narrow size distribution ranging from 40 to 45 nm.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results agree with Kachoei et al 14 Scanning electron microscope images showed spherical ZnO nanoparticles with particle size ranging from 25 to 30 nm. Behroozian et al 19 used SEM technique to evaluate surface pattern of ZnO nanoparticles deposition and showed the presence of spherically shaped ZnO nanoparticles on the wire. Kachoei et al 20 confirmed a uniform coating of spherical shaped ZnO nanoparticles on stainless steel wires with narrow size distribution ranging from 40 to 45 nm.…”
Section: Discussionmentioning
confidence: 99%
“…The frictional force was recorded as 1.227 N in the coated wires and 1.642 N for the non-coated wires. Also, Behroozian et al 19 studied the ZnO nanoparticles coating effect on the frictional resistance between ceramic brackets and orthodontic wires, and reported that the ZnO nanoparticles deposition had significantly decreased the frictional forces between brackets and stainless steel wires.…”
Section: Mechanical Propertiesmentioning
confidence: 99%
“…It is important to underline, that ZnO and CuO coated brackets have been observed with better antimi-crobial characteristics on Streptococcus mutans than when the brackets were coated with CuO nanoparticles alone [ 77 ]. Kachoei et al [ 78 ], Behroozian et al [ 79 ] and Goto et al [ 80 ] proved, that following ZnO nanoparticle coating, the frictional forces be-tween archwires and brackets significantly decreased. Because of that effect, these na-noparticles offer new opportunities in overcoming the unwanted friction forces, better anchorage control, and reduced risk of resorption.…”
Section: Nanomaterials In Orthodonticsmentioning
confidence: 99%
“…Furthermore, reduced frictional forces between wires and brackets have been previously reported which might contribute to a significant reduction in friction during tooth movement [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%